Job Displacement and the Duration of Joblessness: The Role of Spatial Mismatch - Andersson, Fredrik; Haltiwanger, John C.; Kutzbach, Mark J.; Pollakowski, Henry O.; Weinberg, Daniel H. (The Review of Economics and Statistics, 2018)
This paper presents a new approach to the measurement of the effects of spatial mismatch that takes advantage of matched employeremployee administrative data integrated with a person-specific job accessibility measure, as well as demographic and neighborhood characteristics. We focus on a group of job searchers for plausibly exogenous reasons: lower-income workers with strong labor force attachment separated during a mass layoff. Our results support the spatial mismatch hypothesis. We find that better job accessibility significantly decreases the duration of joblessness among lower-income displaced workers, especially for blacks, women, and older workers.